2020
DOI: 10.1080/1528008x.2020.1818357
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Hotel Quality Rate Influence the Preparedness against the Effects of Disasters?

Abstract: Heretofore, hotels have experienced different disasters in various places; and the effects have proven the vulnerability of the hospitality industry and the importance of disaster preparedness. Although studies in the field of hotels and disasters have shown the ill-preparedness to the extent that the hoteliers were shocked by the disasters, none of them have considered a framework to measure the disaster preparedness, and the differences in this industry. Therefore, an index-based approach was proposed by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, today, preparedness has become a primary concern for each stage of disaster management. Preparedness has emerged as an important phase in risk management actions that can be implemented at any stage of a disaster (Badri & Kazemi, 2020). Some studies even describe planning as an activity to improve preparedness, such as warning systems, critical resources, knowledge, and detecting risks and difficulties, which generally limit or avoid disaster risks (Raikes et al, 2019).…”
Section: B Hotel Preparednessmentioning
confidence: 99%
See 2 more Smart Citations
“…However, today, preparedness has become a primary concern for each stage of disaster management. Preparedness has emerged as an important phase in risk management actions that can be implemented at any stage of a disaster (Badri & Kazemi, 2020). Some studies even describe planning as an activity to improve preparedness, such as warning systems, critical resources, knowledge, and detecting risks and difficulties, which generally limit or avoid disaster risks (Raikes et al, 2019).…”
Section: B Hotel Preparednessmentioning
confidence: 99%
“…The term refers to a broad range of interconnected issues, from planning to uniformity in preparedness implementation (WHO, 2020). Badri & Kazemi (2020) found that hotel classification or rating plays a role in hotels' preparedness levels during disasters. Meanwhile, the study's findings (Hussain & Kareem, 2020) shed light on guests' expectations when selecting hotels during the pandemic, particularly those that place a premium on preparedness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparedness is one strategy to reduce disasters' negative impact and prevent losses (AlBattat & Mat Som, 2013). On the other hand, Badri & Kazemi (2020) emphasize a correlation between preparedness and the hotel level because this is related to financial resources, human resources, management approaches, hotel facilities, and structures.…”
Section: Asia-pacificmentioning
confidence: 99%
“…Disaster phase consists of three stages: the pre-disaster phase, the emergency response period, and the post-disaster phase (Sutton & Tierney, 2006). In general, Preparedness studies became a concern after the disaster occurred, but now it seems to be the main focus that is dynamic and can be traced to each phase (Badri & Kazemi, 2020). Preparedness becomes an integral part of the tourism crisis management process.…”
Section: Introductionmentioning
confidence: 99%